2014
DOI: 10.1371/journal.pone.0106902
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Cell Kinase Is a Novel Participant in Intestinal Cell Signaling Responses to Protein Malnutrition

Abstract: Nutritional deficiency and stress can severely impair intestinal architecture, integrity and host immune defense, leading to increased susceptibility to infection and cancer. Although the intestine has an inherent capability to adapt to environmental stress, the molecular mechanisms by which the intestine senses and responds to malnutrition are not completely understood. We hereby report that intestinal cell kinase (ICK), a highly conserved serine/threonine protein kinase, is a novel component of the adaptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…This phenomenon is reminiscent of what we observed in the intestinal epithelium where CILK1 expression can be induced under nutritional stress [36] or radiation injury (unpublished data). Conditional KO mouse models will be needed to interrogate the role of CILK1 in the heart under both normal and pathophysiological conditions.…”
Section: Cilk1 In Cardiac Development and Hypertrophysupporting
confidence: 76%
“…This phenomenon is reminiscent of what we observed in the intestinal epithelium where CILK1 expression can be induced under nutritional stress [36] or radiation injury (unpublished data). Conditional KO mouse models will be needed to interrogate the role of CILK1 in the heart under both normal and pathophysiological conditions.…”
Section: Cilk1 In Cardiac Development and Hypertrophysupporting
confidence: 76%
“…As changes in major signaling pathways that govern intestinal cellular response to stress were found in our previous work to occur mostly at 24 h after challenge, we modified our model with weaned mice and gave them the double challenge of a protein-deficient diet and C. parvum infection at the same time, and then examined the early changes at days 1 and 3 postinfection (15). We successfully reproduced the intensified C.…”
Section: Discussionmentioning
confidence: 99%
“…Its antiapoptotic role in intestinal epithelial cells of murine models has been shown in many studies (23, 24, 39). Our previous study demonstrated that the small intestine responds to protein malnutrition by activating major survival pathways and entering a “survival mode” (15). Activation of Akt pathways was found in our previous study and the present study, which may play a role in increasing cellular resistance to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ICK is very similar to MAP kinase in the catalytic domain and contains a MAPK-like TDY motif in its activation loop [3, 4]. By knocking down ICK expression using short-hairpin RNA interference, our work has demonstrated an important role for ICK in the regulation of cell proliferation and survival in vitro [5, 6]. An essential role of ICK in human development emerged from the report of human ECO and ECO-like syndromes whose major clinical features include hydrocephalus, polydactyly and micromelia [1, 7, 8].…”
Section: Introductionmentioning
confidence: 99%